Implementation of the Ummi Method in Learning Al-Qur'an in Tartil at MDTA Al-Faruq Kertasari Ligung Majalengka - Abdul Hanan; Tiya Imtiyazunnisa; Diniatus Salamah; Agus Alamin (Universitas Islam Nusantara, Bandung, 2024)
This study aims to describe the implementation of the Ummi method in learning the Qur'an in tartil at MDTA Al-Faruq Kertasari, Ligung, Majalengka. A qualitative approach was used with data collection through observation, interviews, and documentation from May to July 2023. Data were analyzed using the Miles and Huberman model, including data collection, reduction, and presentation. The results showed that learning with the Ummi method at MDTA Al-Faruq has been going well. The learning process consists of seven stages: opening, apperception, concept planting, concept understanding, skill practice, evaluation, and closing. Supporting factors include the seriousness of the institution, student motivation, good coordination with Umda Majalengka, and the role of a competent coordinator. However, there are obstacles such as limited facilities, non-ideal teacher and student ratios, costs, and not optimal teacher certification. This study provides recommendations for improving the implementation of the Ummi method, not only in MDTA Al-Faruq but also in other formal and non-formal institutions. Applying this method is expected to improve the ability to read the Qur'an trail according to the rules of tajweed science, thus positively influencing students' mental, psychological, and behavior amid modern challenges.